En busca de un tiempo perdido: (O de la crónica judicial histórica, otra reina sin corona) - Orozco Ospina, Julio César (Folios, revista de la Facultad de Comunicaciones y Filología, 2024)
This text is a prelude to the chronicle presented by the journalist Felipe Osorio Vergara: The three loves of the young tailor. Triple infidelity in the City of Antioquia 1777. The exploration of the judicial archives with the aim of reconstruct ing the historical facts is a challenge for journal ists who require mastery of multiple documen tary analysis techniques such as paleography. The crimes and legal processes of the past are not just a whim for the reconstruction of the forgotten events of the past, it is to once again highlight the voice of the characters and social sectors that have been marginalized at different times in history. This text explores the work of the chronicler, which not only consists of narrat ing, but also of in-depth research, interpreting damaged or incomplete documents, and offering a coherent and accessible story to the contem porary reader. The judicial historical chronicle, as a subgenre of the chronicle, not only facilitates the understanding of the past, but also invites us to reflect on the social, cultural and legal values that have shaped daily life in past eras and that have influenced today›s society.